Biện pháp phát triển năng lực giao tiếp cho học sinh lớp 7 qua giờ dạy Thực hành tiếng Việt - Nguyễn, Thị Xuân Mai; Lê, Thị Hoàng Oanh (Tạp chí Giáo dục, 2024)
Developing learners’ competence and qualities is a key goal of educational innovation. Accordingly, the goal of Literature in high schools is to form and develop students’ basic communication skills such as listening, speaking, reading, and writing. In teaching Literature, teaching Practical Vietnamese plays an important role in training communication skills for learners, aiming to develop language competence. This article introduces methods and some measures for teaching Practical Vietnamese in the 7th grade Literature textbook program (series Chan troi sang tao) to contribute to improving students’ language skills. Research results show that Vietnamese teaching needs strong innovation in the direction of promoting learners’ competence, especially communication competence and the competence to use Vietnamese. Therefore, applying measures to improve and develop students’ communication skills is necessary.